Race, ethnicity, and clinical outcome following sport-related concussion: a systematic review - Cook, Nathan E.; Gaudet, Charles E.; Kissinger-Knox, Alicia; Liu, Brian C.; Hunter, Amy A.; Norman, Marc A.; Saadi, Altaf; Iverson, Grant L. (Frontiers in Neurology, 2023)
This systematic review examined whether race or ethnicity are associated with clinical outcomes (e.g., time to return to school/sports, symptom duration, vestibular deficits, and neurocognitive functioning) following sport-related concussion among child, adolescent, or college-aged student athletes. Additionally, this review assessed whether the existing literature on this topic incorporated or included broader coverage of social determinants of health. The online databases PubMed, MEDLINE®, PsycINFO®, CINAHL, Cochrane Library, EMBASE, SPORTDiscus, Scopus, and Web of Science were searched. A total of 5,118 abstracts were screened and 12 studies met inclusion criteria, including 2,887 youth and young adults. Among the included articles, only 3 studies (25%) examined whether race and ethnicity were associated with outcomes following concussion as a primary objective. None of the studies assessed the association between social determinants of health and outcomes following concussion as a primary objective, although 5 studies (41.7%) addressed a social determinant of health or closely related topic as a secondary objective. Overall, the literature to date is extremely limited and insufficient for drawing conclusions about whether race or ethnicity are categorically associated with outcomes from sport-related concussion, or more specifically, whether there are socioeconomic, structural, or cultural differences or disparities that might be associated with clinical outcome.